Perbandingan Koreksi Medan (Terrain Correction) Konvensional dan Modern pada Metode Gravitasi Menggunakan Data DEM ERTM2160 dan SRTM2gravity pada Wilayah Cianjur - Afikatul Awaliyah; Ahmad Fauzi Pohan (Jurnal Fisika Unand, 2024)
A study has been conducted to compare the distribution of anomaly values obtained through conventional and modern terrain correction to identify the subsurface structure of the Cianjur region, especially around the location of the Cugenang Fault. The data used are gravity disturbance data equivalent to Free Air Anomaly (FAA) from GGMplus, ERTM2160 DEM data as topographic data, and modern terrain correction data from SRTM2gravity. Data is processed using Microsoft Excel, Oasis Montaj, and Surfer software. Based on the results of the CBA contour map obtained, the application of SRTM2gravity data as a modern terrain correction provides better results so that subsurface structure modeling will provide more accurate results. The CBA contour map produced from modern terrain correction provides clearer topographic results than conventional terrain correction using ERTM2160 DEM topographic data. Furthermore, using SRTM2gravity modern terrain correction data provides clearer rock density contrast results along the active path of the Cugenang Fault.